A VIRTUAL PIPE RIG FOR TESTING ACOUSTIC LEAK DETECTION CORRELATORS - Brennan, M. J. [UNESP]; Kroll de Lima, F. [UNESP]; Almeida, F. C. L. de [UNESP]; Joseph, P. F.; Crocker, M. J.; Pawelczyk, M.; Pedrielli, F.; Carletti, E.; Luzzi, S. (Int Inst Acoustics & Vibration, 2015)
Acoustic correlators have been used for many years to locate and detect leaks in buried water distribution pipes. Currently, the only way to compare different correlators directly is in the field. This can be problematic as it may be difficult to present exactly the same conditions to each correlator. In recent years, the way in which leak noise propagates in buried water pipes has been determined, and this has enabled the development of a virtual pipe whose behaviour can be simulated in the computer. By coupling the filtering properties of the pipe with electrodynamic shakers, a prototype system has been developed that will allow different correlators to be compared directly in laboratory conditions. Different situations, such as pipe material and size, and measurement positions, as well as leak strength can be simulated. The details of the virtual pipe test-rig are discussed in this paper.